Foundation phase teachers’ experiences in teaching physical education at a primary school in the COVID-19 era in the Motheo district, Free State, South Africa - Patrick Mweli; Lerato Mohale (International Journal of Studies in Inclusive Education)
Foundation phase teachers encountered challenges when teaching physical education and neglected it during the COVID-19 era. They are sometimes unconfident enough to teach it, and its negligence could affect learners’ physical, social, and emotional development. This study explores the experiences of the foundation phase teachers in teaching physical education at school. This employed a qualitative approach and phenomenological research design. The results revealed that foundation phase teachers had experiences and challenges teaching physical education at a primary school during COVID-19 in the Motheo district, Free State, South Africa. Furthermore, this study recommends teaching and learning support to help teachers and pre-service teachers improve their practice before they become in-service teachers and advocate for physical education.